Effect of waste rock inclusions on the seismic stability of an upstream raised tailings impoundment: A numerical investigation - Ferdosi, Behnam; James, M.; Aubertin, M. (2015)
© 2015, National Research Council of Canada. All rights reserved. Over the years, seismic activity has been a relatively common cause of tailings impoundment failure. The flow of liquefied tailings from such ruptures can result in very severe consequences, including loss of life and environmental damage. A co-disposal technique consisting of placing waste rock inclusions in tailings impoundments prior to and during tailings deposition was proposed by the authors. The waste rock is placed to create continuous inclusions within the impoundment, which provide a number of environmental and geotechnical benefits, particularly with respect to seismic stability. The results of numerical simulations previously performed have shown that the UBCSAND model can predict the seismic response of tailings. The UBCSAND constitutive model was used to conduct simulations to evaluate of the use of waste rock inclusions to improve the seismic stability of a tailings impoundment. The evaluation consists of numerical analyses of an actual tailings impoundment as constructed (without inclusions), and then assuming that it was constructed with inclusions, subjected to earthquake loads of various energy contents and with different predominant frequencies. The analyses were conducted in static, seismic, and post-shaking phases. The displacement of the surface of downstream slope of the tailings dyke was recorded during the analyses. The results indicate that the presence of waste rock inclusions can significantly improve the seismic behavior of the impoundment by reducing the displacements of the surface of the downstream slope and the extent of potential failure zones. Also, the results show that in most cases, the influence of a low-frequency earthquake on the displacement of the downstream slope of the tailings dyke is more important than that of a high-frequency earthquake. The performances of the tailings impoundment with different configurations of waste rock inclusions (varying width and center-to-center spacing) were classified based on the average normalized horizontal displacement of the downstream slope (ARx) for a range input ground motions. Charts were then developed to show how ARx is influenced by the total width of inclusions, their spacing, and the input ground motions.